An emerging, recognizable facial phenotype in association with mutations in GLI‐similar 3 (GLIS3). Issue 7 (5th May 2016) - Dimitri, Paul; De Franco, Elisa; Habeb, Abdelhadi M.; Gurbuz, Fatih; Moussa, Khairya; Taha, Doris; Wales, Jerry K. H.; Hogue, Jacob; Slavotinek, Anne; Shetty, Ambika; Balasubramanian, Meena
Abstract : Neonatal diabetes and hypothyroidism (NDH) syndrome was first described in 2003 in a consanguineous Saudi Arabian family where two out of four siblings were reported to have presented with proportionate IUGR, neonatal non‐autoimmune diabetes mellitus, severe congenital hypothyroidism, cholestasis, congenital glaucoma, and polycystic kidneys. Liver disease progressed to hepatic fibrosis. The renal disease was characterized by enlarged kidneys and multiple small cysts with deficient cortico‐medullary junction differentiation and normal kidney function. There was minor facial dysmorphism (depressed nasal bridge, large anterior fontanelle, long philtrum) reported but no facial photographs were published. Mutations in the transcription factor GLI‐similar 3 ( GLIS3 ) gene in the original family and two other families were subsequently reported in 2006. All affected individuals had neonatal diabetes, congenital hypothyroidism but glaucoma and liver and kidney involvement were less consistent features. Detailed descriptions of the facial dysmorphism have not been reported previously. In this report, we describe the common facial dysmorphism consisting of bilateral low‐set ears, depressed nasal bridge with overhanging columella, elongated, upslanted palpebral fissures, persistent long philtrum with a thin vermilion border of the upper lip in a cohort of seven patients with GLIS3 mutations and report the emergence of a distinct, probably recognizable facial gestalt in this group which evolves with age. © 2016 Wiley Periodicals, Inc.